Effect of daily consumption of probiotic yoghurt on albumin to creatinine ratio, eGFR and metabolic parameters in patients with type 2 diabetes with microalbuminuria: study protocol for a randomised controlled clinical trial - Alireza Esteghamati; Ahmad Esmaillzadeh; Seyed Mojtaba Ghoreishy; Nooshin Shirzad; Manouchehr Nakhjavani; Kurosh Djafarian (BMJ Open)
Introduction To alleviate clinical symptoms of diabetic nephropathy (DN), several dietary and non-dietary strategies have been suggested. Probiotic-enriched foods, through their effects on modulating microflora, might help these patients control the adverse effects. The current study will be done to examine the effects of probiotic yoghurt consumption on albumin to creatinine ratio, estimated glomerular filtration rate (eGFR) and metabolic parameters in patients with type 2 diabetes with nephropathy.Methods and analysis Sixty patients with DN will be recruited in this study. After block matching for sex, body mass index and age, patients will be randomly assigned to receive 300 g/day probiotic yoghurt containing 106 CFU/g Lactobacillus acidophilus and Bifidobacterium lactis strains or 300 g/day plain yoghurt daily for 8 weeks. Weight, height and waist circumference will be measured at study baseline and after the intervention. Biochemical indicators including glycaemic measures (haemoglobin A1c (HbA1c), fasting blood sugar (FBS)), inflammatory markers (high sensitivity-C reactive protein), lipid profile (total cholesterol (TC), triglyceride (TG), low-density lipoprotein (LDL), high-density lipoprotein (HDL)) and finally renal makers (creatinine, albumin to creatinine ratio, eGFR) will be assessed at study baseline and at the end of the trial.Discussion Improving the condition of a person with DN is a serious clinical challenge. The use of probiotic supplements has been considered in these people, but the use of probiotic-enriched foods has received less attention.Trial registration number Iranian Registry of Clinical Trials (www.irct.ir) (IRCT20201125049491N1).